In vitro evaluation of photon and raster-scanned carbon ion radiotherapy in combination with gemcitabine in pancreatic cancer cell lines - El-Shafie, Rami; Habermehl, Daniel; Rieken, Stefan; Mairani, Andrea; Orschiedt, Lena; Brons, Stephan; Haberer, Thomas; Weber, Klaus-Josef; Debus, Jürgen; Combs, Stephanie (Journal of radiation research, 2013)
Background: Pancreatic cancer is the fourth leading cause of cancer deaths, being responsible for 6% of all cancer-related deaths. Conventional radiotherapy with or without additional chemotherapy has been applied in the past in the context of neoadjuvant or adjuvant therapy concepts with only modest results, however new radiation modalities, such as particle therapy with promising physical and biological characteristics, present an alternative treatment option for patients with pancreatic cancer. Up until now the raster scanning technique employed at our institution for the application of carbon ions has been unique, and no radiobiological data using pancreatic cancer cells has been available yet. The aim of this study was to evaluate cytotoxic effects that can be achieved by treating pancreatic cancer cell lines with combinations of X-rays and gemcitabine, or alternatively with carbon ion irradiation and gemcitabine, respectively. Materials and Methods: Human pancreatic cancer cell lines AsPC-1, BxPC-3 and Panc-1 were irradiated with photons and carbon ions at various doses and treated with gemcitabine. Photon irradiation was applied with a biological cabin X-ray irradiator, and carbon ion irradiation was applied with an extended Bragg peak (linear energy transfer (LET) 103 keV/μm) using the raster scanning technique at the Heidelberg Ion Therapy Center (HIT). Responsiveness of pancreatic cancer cells to the treatment was measured by clonogenic survival. Clonogenic survival curves were then compared to predicted curves that were calculated employing the local effect model (LEM). Results: Cell survival curves were calculated from the surviving fractions of each combination experiment and compared to a drug control that was only irradiated with X-rays or carbon ions, without application of gemcitabine. In terms of cytotoxicity, additive effects were achieved for the cell lines Panc-1 and BxPC-3, and a slight radiosensitizing effect was observed for AsPC-1. Relative biological effectiveness (RBE) of carbon ion irradiation ranged from 1.5-4.5 depending on survival level and dose. Sensitizer enhancement ratio (SER) values calculated at 10% cell survival ranged from 1.24-1.66, depending on cell line, gemcitabine dose and irradiation modality. Experimentally ascertained survival curves matched those predicted by LEM-calculation. Conclusion: Our experiments have shown a combined treatment of irradiation and chemotherapy with gemcitabine to be a good means of achieving additive cytotoxic effects on pancreatic cancer cell lines. The data generated in this study will serve as radiobiological basis for further preclinical and clinical studies.